Basic Life Support in 9th Grade: Teaching Methodologies from Students' View - Maria Boné; Natália Oliveira; Jorge Bonito (Instituto Politécnico de Viseu, 2024)
Introduction: Cardiopulmonary resuscitation (CPR) performed by bystanders is more effective than any other therapeutic intervention following an out-of-hospital cardiac arrest. International organizations emphasize the need for high-quality training for bystanders in CPR, promoting confidence and proficiency to act in emergencies. In Portugal, the teaching basic life support (BLS) in the 9th grade within the Natural Sciences subject began in the academic year 2015-2016. Objective: To acknowledge students' perceptions about the methodologies used in teaching BLS to 9th-grade students. Methods: This is a descriptive, cross-sectional, and analytical survey-type study, in which a representative sample of students (n=1215) responded to a questionnaire, between April and June 2020. Results: BLS was not studied by 10.4% of the respondents. Among those who studied the subject, a modal value of 3-4 hours was dedicated to BLS in the 9th grade. This subject was taught by firefighters, nurses, or other professionals who were no teachers in 26.1% of the cases. Students pointed out the lack of practical simulations and the need to be learn the pediatric BLS protocol, besides with a different approach. Conclusion: Practical training was perceived by students as a very weak component, and in some cases, it took place without mannequins, videos or qualified teachers. Teaching and learning BLS in Portuguese schools is far from ideal for such an essential subject.